2012
DOI: 10.2460/ajvr.73.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tyrosinase expression in canine and equine melanocytic tumors

Abstract: In the present study, the methods used were highly sensitive and specific for detection of tyrosinase expression in equine and canine tumors, and overexpression of this transcript in melanomas was detected. This suggested that a DNA vaccine developed for use in dogs with melanoma that targets tyrosinase may be considered for use in other affected species, such as horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…In general, tyrosinase expression is tightly controlled both spatially and temporally [21]. In tumor tissue, however, tyrosinase expression appears to be constitutively increased [21][22][23]. Furthermore, gray horses at increased risk of tumor formation (ADE Â 2) would be expected to have elevated tyrosinase expression in their melanocytes due to enhanced signaling from the MC1R pathway [18,21,24].…”
Section: Introductionmentioning
confidence: 97%
“…In general, tyrosinase expression is tightly controlled both spatially and temporally [21]. In tumor tissue, however, tyrosinase expression appears to be constitutively increased [21][22][23]. Furthermore, gray horses at increased risk of tumor formation (ADE Â 2) would be expected to have elevated tyrosinase expression in their melanocytes due to enhanced signaling from the MC1R pathway [18,21,24].…”
Section: Introductionmentioning
confidence: 97%
“…Tyrosinase expression in human melanoma cell lines is variable, thus leading Chen and colleagues to propose that tumours with low levels of tyrosinase expression are poor targets of tyrosinase-specific immunotherapy (Chen et al, 1995). In contrast, a CMM study revealed strong tyrosinase and MHCI mRNA expression in all tumours evaluated irrespective of the degree of tumour pigmentation (Phillips et al, 2012). It should be noted, however, that although these mRNA data are supportive of active gene transcription, one could not conclude that the encoded proteins are properly translated, proteolytically processed and correctly oriented within the cell, which is of key importance to effective antigen presentation (York and Rock, 1996).…”
Section: Possible Immunological Reasons For Lack Of Efficacymentioning
confidence: 99%
“…1,4,16,24,27 In horses, S100 protein is the marker consistently expressed in melanocytic neoplasms. 22 Tyrosinase expression has been detected by immunohistochemistry or molecular methods in equine melanomas, 11,23 but benign equine melanocytic tumors apparently do not express tyrosinase. 23 Monoclonal antibody HMB-45, which recognizes the melanocytic differentiation antigen gp 100, is also expressed in equine malignant melanomas.…”
mentioning
confidence: 99%